Use of Information Technology in Library & Information Education - Murthy, S.S. (DESIDOC Journal of Library & Information Technology, 2003)
IT covers areas which can be grouped into the broad disciplines of computers and communications covering the development and management of information systems like libraries, databases and networks-both online and off-line and reprography and mass communication covering the technologies used for presentation and dissemination of information. This paper briefly discusses the impact and use of all these technologies on library and information science (LIS) education. http://dx.doi.org/10.14429/dbit.17.2.3334